Failure Mechanisms of Fiber Optic Temperature Sensors in High Temperature and Vibration Environments. Issue 35 (15th July 2016) - Tsakalakos, Loucas; Dani, Uttara A.; Lee, Boon K.; Lee, Susanne M.; Mandal, Sudeep; Smentkowski, Vincent; Soni, Sunilkumar
ABSTRACT: Fiber optic temperature sensors are used in a variety of harsh environment applications. We have explored use of such temperature sensors in commercial gas turbines to measure the temperature at various regions of interest within the turbine system. More specifically, fiber optic temperature rakes were designed and installed on a commercial gas turbine under full load conditions. This work will focus on failure mechanisms observed at multiple length scales that impact the performance of high temperature optical fiber sensors. It was found that Au-coated silica fibers, which are a standard in the industry, undergo various failure modes when subjected to combinations of high temperature and high vibration. More specifically, the Au coating became soft/ductile as the temperature is increased. We also observed that the Au coating was not well bonded to the silica fiber, as expected since there were no adhesion layers present. These effects led to significant damage of the fiber optic under high vibrations. We also found that vibrations from the gas turbine coupled into fundamental modes of the fiber optic probe assembly, which were analyzed by detailed dynamic mechanical analysis. This led to the fiber impacting the internal wall of the probe assembly, which caused further damage and failure of the fiber and the Au coating. The silica fibers returned from the field also exhibited significant twisting throughout most of their length. This suggests the fibers reached temperatures above their strain point (about 1000 C for pure silica glass), which is explained by either a) the strain point had been significantly reduced by the presence of the Ge dopant, or b) the temperature was higher than expected in the gas turbine exhaust region. It was also hypothesized that complex anelastic effects may play a role under the high temperature, high vibration environment experienced by the probes. Detailed structural analysis of the fiber optic temperature sensors by scanning electron microscopy, ToF-SIMS, and X-ray microscopy will be presented to corroborate the above simulations and proposed damage mechanisms. Finally, we note that the fiber Bragg gratings (FBG) present within the temperature probes provided promising temperature data, and were in fact not damaged/erased by the high temperature environment.